Project-Oriented Work in Slovenian Manufacturing Companies - Palčič, Iztok; Buchmeister, Borut; Lalić, Bojan (International Journal of Industrial Engineering and Management, 2013)
This paper deals with the characteristics of project-oriented work in Slovenian manufacturing companies. First part of the paper focuses on the use of project management in manufacturing environment. This is followed by the presentation of the results of the largest European manufacturing survey, conducted in years 2009 and 2012. Slovenian questionnaire partly consists of questions that explore the characteristics of project-oriented work in Slovenian manufacturing companies. The results indicate that the project-oriented work is widely used in Slovenian manufacturing companies, which implemented different project types in their environment in the period from 2007 to 2012. We have compared several production characteristics between those companies which have introduced project-oriented work with those, which decided not to introduce it. One of the most important findings is the fact that the share of companies, which implement different project types dropped heavily between 2007-2009 and 2010-2012 period. Article history: Received (12.12.2012); Revised (23.05.2013); Accepted (28.06.2013)